Proyecto de factibilidad para la implementación de una empresa lavadora de automóviles mediante autoservicio, en el cantón Lago Agrio, provincia de Sucumbíos - Quezada Calva, María Magdalena (2017)
The objective of the present investigation is to determine the commercial feasibility of the proposed implementation of a self-service car washing company in the canton Lago Agrio of the province of Sucumbíos, in the first instance the methods were used as the Inductive, Deductive , Statistical and Bibliographic. The use of all these methods allowed us to reach the culmination of the present work since to achieve this we had to follow the steps of application, understanding and demonstration. In the market study conducted in the canton of Lago Agrio, with a sample of 381 people and 6 washing machines; The results were analyzed and the results were then inferred and then the market analysis was carried out, determining the Potential Demand of 46,171 vehicles, Real Demand 24,471 vehicles, Effective Demand 466,900 vehicular washes, The Offer of 47,580 washes and the Unsatisfied Demand of 419,320 washes, which allowed to determine that the project can and should be executed, due to the results obtained in the analysis of the demand, supply and levels of commercialization of this service. The installed capacity of the project determines that the company will be able to offer 43,680 washes and the used capacity will be 43,680 washes, of which 100% of the capacity will be used for the first year corresponding to 43,680 washes, in addition it is determined the location of the same that will be located in the city of Lago Agrio, in the streets 10 de Agosto km. 6 via Quito San Jose sector. The service process demands the use of suitable machines and equipment, which will guarantee a quality product at moderate prices. Next, the engineering of the project is developed, determining the process diagrams, operational and management characteristics, technical requirements such as equipment, installations, furniture and appliances. Likewise, an administrative study was carried out, determining as a Limited Liability Company, and with the functional organizational structure at the hierarchical levels, both Legislative, Executive, Adviser Level, Support Level, Operational Level, as well as function manuals, organizational charts; which served as guidelines for implementing a good organization. The project reaches an investment of 68,852.40 dollars and will be financed with a contribution of the partners 67% of the total of the investment that corresponds to 45.852.40 dollars and a loan that will maintain the project with Banecuador will constitute the 33% that corresponds to $ 23,000.00 3 year term at 15% annual interest. The financial evaluation presents the following results: According to the NPV of the present project gives us a positive value of $ 3,740.70, indicating that the project or investment is convenient. For the present project, the TIR is 16.40%, this value being satisfactory to carry out the project, the time that would be required to recover the original investment would be 4 years, 2 months and 3 days, for the present project, the sensitivity values are less than one, therefore changes in costs and revenues increased by 5% and decreased by 3% respectively, ie the project is not sensitive to these changes. Subsequently, the most significant conclusions and recommendations of the project.